Host and Viral Modulation of RIG-I-Mediated Antiviral Immunity - Liu, Yiliu; Olagnier, David; Lin, Rongtuan (Frontiers in Immunology, 2017)
Innate immunity is the first line of defence against invading pathogens. Rapid and efficient detection of pathogen-associated molecular patterns (PAMPs) via pattern recognition receptors (PRRs) is essential for the host to mount defensive and protective responses. Retinoic acid inducible gene-I (RIG-I) is critical in triggering antiviral and inflammatory responses for the control of viral replication in response to cytoplasmic virus-specific RNA structures. Upon viral RNA recognition, RIG-I recruits the mitochondrial adaptor protein MAVS which leads to a signaling cascade that coordinates the induction of type I IFNs, as well as a large variety of antiviral IFN-stimulated genes. The RIG-I activation is tightly regulated via various posttranslational modifications for the prevention of aberrant innate immune signaling. By contrast, viruses have evolved mechanisms of evasion, such as sequestrating viral structures from RIG-I detections and targeting receptor or signaling molecules for degradation. These virus-host interactions have broadened our understanding of viral pathogenesis and provided insights into the function of the RIG-I pathway. In this review, we summarize the recent advances regarding RIG-I pathogen recognition and signaling transduction, cell-intrinsic control of RIG-I activation, and the viral antagonism of RIG-I signaling.